Pelaksanaan Program Pengelolaan Penyakit Kronis (Prolanis) - Siral Siral; Riska Yanuarti; Eva Oktavidiati; Nopia Wati; Wulan Angraini; henni febriawati (Citra Delima Scientific journal of Citra Internasional Institute, 2023)
The visit of Hypertension and Diabetes Mellitus suffers who are members og the Chronic Disease Management Program (PROLANIS) are quite high with 576 visits. Puskesmas Jalan Gedang Kota Bengkulu has the highest number of visits to 10 other Puskesmas. The purpose og this study is to detemine the implementation of PROLANIS program Puskesmas Jalan Gedang, Bengkulu City. This study used a qualitative method. The informants have been involved in this study were 8 people consisting of 1 head of Puskesmas, 1 BPJS officer, 1 Person in charge of PROLANIS, and 5 PROLANIS participants. The data of the study were analyzed through data reduction, data review, and drawing conclusions or verification. PROLANIS program policy has been programmed and planned according to the provisions. Personnel involved in PROLANIS activities were, health workers, BPJS parties, PROLANIS cadres and PROLANIS members. The process of conducting medical consultations for PROLANIS participants, cadres abd health workers, and education of PROLANIS participant groups with questions and answers and providing information, the home visit was less than optimal due to lock of the time and extensive work area of the puskesmas. Remembers sms program was still not optimally done, if there was a change in the schedule of PROLANIS activities were gymnastics.